2019
DOI: 10.1038/s41598-019-50253-6
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital lactate improves prediction of the need for immediate interventions for hemorrhage after trauma

Abstract: The blood lactate level is used to guide the management of trauma patients with circulatory disturbance. We hypothesized that blood lactate levels at the scene (Lac scene) could improve the prediction for immediate interventions for hemorrhage. We prospectively measured blood lactate levels and assessed retrospectively in 435 trauma patients both at the scene and on arrival at the emergency room (ER) of a level I trauma center. Primary outcome was immediate intervention for hemorrhage defined as surgical/radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Lactate concentration is widely used as an indicator of tissue hypoperfusion and hypoxia in critically ill patients and as a biomarker to determine response of the therapy or to predict outcome of the disease (Fukuma et al 2019;Shapiro et al 2005, Sharkey and Wellman, 2013, Vandromme et al 2010. As the end product lactate forms primarily during anaerobic glycolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate concentration is widely used as an indicator of tissue hypoperfusion and hypoxia in critically ill patients and as a biomarker to determine response of the therapy or to predict outcome of the disease (Fukuma et al 2019;Shapiro et al 2005, Sharkey and Wellman, 2013, Vandromme et al 2010. As the end product lactate forms primarily during anaerobic glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Vital signs are often used as an initial measure of hemodynamic stability in both humans and animals, but studies prove that they might grossly underestimate the depth of shock (Basel et al 2007;Scalea et al 1998). There are numerous studies, which investigate central venous oxygen saturation, base deficit and lactate changes being more accurate than vital signs (Basel et al 2007;Davis et al 1996;Fukuma et al 2019;Scalea et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we showed no in uence of transport on in-hospital mortality. Other studies did no report strong evidence of any bene ce of HEMS on in-hospital mortality among injured patients (31,32,33) Fukuma et al showed that physiological variables plus lactate on-scene signi cantly increased the predictive value for immediate intervention for hemorrhage (Area Under the Curve 0.882, 95% CI 0.839-0.925) compared to that using physiological variables only (AUC 0.837, 95% CI 0.787-0.887, p = 0.0073) (34). It may be interesting to investigate the role of on-scene lactate measuring during eld triage and its impact on undertriage.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 reports injuries characteristics and outcome of injured patients. ISS was higher in correct-triaged patient (25 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] vs 21.5 [17][18][19][20][21][22][23][24][25][26][27][28][29], p < 0.0001)). The most frequent severely injured (AIS ≥ 3) body areas were head (53.57%) and thorax (54.11%).…”
Section: Overall Characteristicsmentioning
confidence: 99%
“…Nevertheless, we showed no in uence of transport on in-hospital mortality. Other studies did no report strong evidence of any bene ce of HEMS on in-hospital mortality among injured patients (31,32,33) Fukuma et al showed that physiological variables plus lactate on-scene signi cantly increased the predictive value for immediate intervention for hemorrhage (Area Under the Curve 0.882, 95% CI 0.839-0.925) compared to that using physiological variables only (AUC 0.837, 95% CI 0.787-0.887, p = 0.0073) (34). It may be interesting to investigate the role of on-scene lactate measuring during eld triage and its impact on undertriage.…”
Section: Discussionmentioning
confidence: 99%